TAXONOMY OF THREE TAXA OF BULBOCHAETE C. AG. AND PHYSICO-CHEMICAL ANALYSIS OF WATER IN WEST BENGAL, INDIA - Halder, Nilu (Ecoprint: An International Journal of Ecology, 2016)
In the present paper, altogether three algal taxa of genus Bulbochaete C. Ag. (Oedogoniales, Chlorophyceae) viz. Bulbochaete elatior f. pumila Hirn, Bulbochaete pseudoelatior Jao and Bulbochaete triangularis var. bengalensis J.P. Keshri have been morpho-taxonomically described with physico-chemical characterization of water and some additional information. These algal samples were collected as epiphytic conditions on submerged stems of angiospermic plants from two freshwater ponds in Hooghly district, West Bengal, India. All these three species are new records from this region. They were greenish, nannandrous, gynandrosporous or idioandrosporous. Most importantly, phenotypically their oospore shape was more or less alike as oogonium. The results of analyses of physico-chemical parameters of water showed that pH ranged from 7.2-7.4 (alkaline). The primary nutrients like nitrate-nitrogen (NO3-N) and phosphate (PO43-) values were measured in lower amounts (0.15-0.17 mg/l and 0.23-0.24 mg/l, respectively) which affected Bulbochaete growth and diversity in the lentic water bodies. It was interesting to note that winter season was suitable for their occurrences. ECOPRINT 23: 13-18, 2016